Lactobacillus delbrueckii CIDCA 133 Ameliorates Chemotherapy-Induced Mucositis by Modulating Epithelial Barrier and TLR2/4/Myd88/NF-κB Signaling Pathway - Barroso, Fernanda Alvarenga Lima; de Jesus, Luís Cláudio Lima; da Silva, Tales Fernando; Batista, Viviane Lima; Laguna, Juliana; Coelho-Rocha, Nina Dias; Vital, Kátia Duarte; Fernandes, Simone Odília Antunes; Cardoso, Valbert Nascimento; Ferreira, Enio; Martins, Flaviano Santos; Drumond, Mariana Martins; et al. (Frontiers in Microbiology, 2022)
Intestinal mucositis promoted by the use of anticancer drugs is characterized by ulcerative inflammation of the intestinal mucosa, a debilitating side effect in cancer patients undergoing treatment. Probiotics are a potential therapeutic option to alleviate intestinal mucositis due to their effects on epithelial barrier integrity and anti-inflammatory modulation. This study investigated the health-promoting impact of Lactobacillus delbrueckii CIDCA 133 in modulating inflammatory and epithelial barrier markers to protect the intestinal mucosa from 5-fluorouracil-induced epithelial damage. L. delbrueckii CIDCA 133 consumption ameliorated small intestine shortening, inflammatory cell infiltration, intestinal permeability, villus atrophy, and goblet cell count, improving the intestinal mucosa architecture and its function in treated mice. Upregulation of Muc2, Cldn1, Hp, F11r, and Il10, and downregulation of markers involved in NF-κB signaling pathway activation (Tlr2, Tlr4, Nfkb1, Il6, and Il1b) were observed at the mRNA level. This work suggests a beneficial role of L. delbrueckii strain CIDCA 133 on intestinal damage induced by 5-FU chemotherapy through modulation of inflammatory pathways and improvement of epithelial barrier function.